Reversible Data Hiding in Encrypted Domain Based on the Error-Correction Redundancy of Encryption Process - Kong Yongjun (Security and Communication Networks, 2022)
The existing reversible data hiding methods in encrypted domain separate image encryption from information embedding and do not make full use of the redundant space in the process of image encryption. In order to improve the performance of reversible data hiding by using the technical characteristics of image encryption, a reversible data hiding method based on McEliece error correction is proposed. Firstly, the segmentation position of bit plane is determined according to the embedding requirement and texture characteristic, and the image is divided into high and low significant bits. Secondly, because of the error-correcting characteristic of McEliece encryption, reversible data embedding can be realized while encrypting low significant bits. Then, the high significant bits are compressed to reserve space for the ciphertext extension of the low significant bits. Finally, the whole high significant bits information is stream-encrypted. As long as the image receiver has the decryption key, the image can be restored without distortion. By concealing the relationship between error correction and secret information mapping, the concealment of secret information transmission can be realized. In addition, due to different processing for different pixels, it can be efficiently transmitted with low computational complexity for applications that only need general images. The simulation results show that this scheme can not only realize the separable operation of information extraction and image recovery but also resist the noise attack to a certain extent. The maximum embedding rates of 10 standard images from USC-SIPI and 50 standard images from BOSS-BASE are 2.228 and 2.323 bpp, respectively.